Comparative Analysis Of Cellular Beam And Honeycomb Beam With Anasys Program - Alvin Hogan M. Situmorang (IHSA Institute, 2021)
Steel is one of the most widely used construction materials. Along with the development of technology in the field of construction, many variations have been made in the use of steel as a construction material to make it more suitable for the needs and economical in terms of cost. One of the innovations that is often used in steel is to make holes in the body to increase the height of the steel profile. The shape of the hole that is usually formed on the body varies. The most frequently used variations are the hexagon shape (honeycomb beam) and the circular beam (cellular beam). In this study, we will compare the honeycomb beam and the cellular beam. The two beams will be made in several variations with D/Do and S/Do parameters. The experiment was carried out using the ANSYS program. Comparisons are made to find a beam that has a better ability than the parameter variations on the two beams From the results of the study, it was found that the best parameter variations were D/Do = 1.6 and S/Do = 1.08 for honeycomb beam. For cellular beam D/Do = 1.6 and S/Do = 1.28 which is better. Then from the comparison of cellular beam and honeycomb beam, it is found that the honeycomb beam is better.